Coastline Analysis Using Remote Sensing Applications in Untia Coastal Areas Makassar City South Sulawesi Province - Danial, Danial; Asmidar, Asmidar; Syahrul, Syahrul; Hamsiah, Hamsiah; W. Ningsih, Nining (Agrikan Jurnal Agribisnis Perikanan, 2021)
This research was conducted with a remote sensing analysis approach with a comparative causal method, namely a multitemporal image comparison method to see the changes that occur, which are divided into three stages: image processing, field surveys and secondary data procurement, as well as advanced data processing. Through processing overlapping coastline maps can also be obtained from changes in coastline over the past 5 years. In 2013-2014 there was reclamation of 0.22 ha, in 2014-2015 there was an abrasion of 0.46 ha, and the addition of mangroves covering 1.07 ha in the coastal area of Untia. In 2015-2016 there was reclamation with an area of 0.9 ha, the addition of mangrove area of 2.84 ha and abrasion of 0.02 ha. And in 2016-2017 there was a change in the area due to reclamation reaching 9.79 ha. The extent of the change in coastline in the Untia Village, Biringkanaya District is 15.3 ha.